How to Predict the Long-term Course of Neurodegenerative Diseases? - Montolío Marco, Alberto; Cegoñino Banzo, José; García Martín, Elena; Pérez del Palomar Aldea, Amaya (Jornada de Jóvenes Investigadores del I3A, 2020)
The aim of this work is to predict the disability state in neurodegenerative disease, such as multiple sclerosis (MS), using clinical batabases and machine learning techniques. This prediction could help clinicians select a more specific treatment for MS patients.